Novel Sigma-1 receptor antagonists: from opioids to small molecules: what is new?. (January 2018) - Arena, Emanuela; Dichiara, Maria; Floresta, Giuseppe; Parenti, Carmela; Marrazzo, Agostino; Pittalà, Valeria; Amata, Emanuele; Prezzavento, Orazio
Sigma-1 (σ1 ) receptor has been identified as a chaperone protein that interacts with other proteins, such as N -methyl-D-aspartate (NMDA) and opioid receptors, modulating their activity. σ1 receptor antagonists have been developed to obtain useful compounds for the treatment of psychoses, pain, drug abuse and cancer. Some interesting compounds such as E-5842 (5 ) and MS-377 (24 ), haloperidol and piperazine derivatives, respectively, were endowed with high affinity for σ1 receptors (Ki σ1  = 4 and 73 nM; Ki σ2  = 220 and 6900, respectively). They were developed for the treatment of psychotic disorders and5 also underwent Phase II clinical trials suggesting interesting potential therapeutic applications. Here, σ1 receptor antagonists have been grouped based on chemical structure and reviewed according to structure–activity relationship and potential therapeutic role.